2019
DOI: 10.1111/papt.12261
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ingroup identity and Paranoid ideation among people from African and African Caribbean backgrounds

Abstract: Objectives: People from ethnic minority groups experience higher rates of paranoid delusions compared with people from ethnic majority groups. Identifying with social groups has been shown to protect against mental health symptoms; however, no studies have investigated the relationship between social identification and paranoia in ethnic minority populations. Here, we investigated the association between British identification and paranoia in a sample of people from African and African-Caribbean backgrounds li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
(130 reference statements)
1
5
0
Order By: Relevance
“…The results are consistent with past research indicating an association between neighbourhood identification and better mental health (Cruwys et al, 2014;Elahi et al, 2018;McIntyre et al, 2019;McIntyre et al, 2018a;McIntyre et al, 2018b), but for the first time extend these effects to self-harm. The results reflect the possibility that identifying more with one's neighbourhood helps protect against self-harm thoughts and behaviours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results are consistent with past research indicating an association between neighbourhood identification and better mental health (Cruwys et al, 2014;Elahi et al, 2018;McIntyre et al, 2019;McIntyre et al, 2018a;McIntyre et al, 2018b), but for the first time extend these effects to self-harm. The results reflect the possibility that identifying more with one's neighbourhood helps protect against self-harm thoughts and behaviours.…”
Section: Discussionsupporting
confidence: 91%
“…Social identification with one's current home town has also been shown to protect people against the negative impact of stress on anxiety, depression, and paranoia (Elahi et al, 2018). These effects may be particularly potent in vulnerable groups, such as young people (McIntyre et al, 2018b) and ethnic minority populations (McIntyre et al, 2019;McIntyre et al, 2016). Moreover, there is strong evidence of a relationship between feeling a sense of belonging to social groups and lower levels of depression (Cruwys et al, 2014), and that social identity interventions are associated with reductions in depression and anxiety (Haslam et al, 2016).…”
Section: Does Neighbourhood Identification Buffer Against the Effects...mentioning
confidence: 99%
“…A subsequent study of UK African-Caribbean adults found a more complex relationship between ethnic identity and paranoia. In this study, participants who strongly identified as being British, but who experienced high levels of negative contact with the majority White British population, were more likely to experience paranoia ( McIntyre et al, 2019 ). This finding suggests that the effects of social identities may be positive or negative contingent on the quality of contact with other people from the ingroup.…”
mentioning
confidence: 71%
“…In addition, in the present study, psychological mediators were not tested. In future studies, it would be useful to assess whether self-esteem ( Elahi et al, 2018 ) and/or locus of control ( McIntyre et al, 2019 ) mediate the relationship between perceived discrimination and mental health in the Pakistani community, as has been found in studies examining other stressors and populations.…”
Section: Discussionmentioning
confidence: 99%
“… 116 , 117 For example, research among Black Britons found that identifying more with their racial identity was associated with higher levels of paranoia if their interactions with White Britons were mostly negative. 118 This suggests that when individuals have a stigmatized identity, experiences of prejudice and discrimination related to that identity can result in mental distress.…”
Section: Discussionmentioning
confidence: 99%